2013
DOI: 10.1111/mpp.12098
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the transcriptome of Hirschmanniella oryzae to explore potential survival strategies and host–nematode interactions

Abstract: The rice root nematode Hirschmanniella oryzae is the most abundant plant-parasitic nematode in flooded rice fields and is distributed world-wide. Although it is economically less important than sedentary nematodes, it can cause severe yield reductions and economic losses in specific environmental conditions. No transcriptome data for this genus were available until now. We have performed 454 sequencing on a mixed life stages population to gain an insight into nematode-plant interactions and nematode survival s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 76 publications
(98 reference statements)
0
29
1
Order By: Relevance
“…They mainly provide platforms to assemble proteins or nucleic acids into functional complexes. The abundance of similar protein families has been reported for other parasitic nematodes, such as the rice pathogen Hirschmanniella oryzae (Bauters et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…They mainly provide platforms to assemble proteins or nucleic acids into functional complexes. The abundance of similar protein families has been reported for other parasitic nematodes, such as the rice pathogen Hirschmanniella oryzae (Bauters et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…coffeae [ 10 ], P . thornei [ 11 ], and Hirschmanniella oryzae [ 65 ], but absent in P . zeae transcriptome [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, GH5 cellulases, GH30 xylanases, GH28 polygalacturonases, GH32 candidate invertases, PL3 pectate lyases, L-threonine aldolases, candidate phosphoribosyltransferases, GH43 candidate arabinanases, GH53 candidate arabinogalactanase, chorismate mutases, expansin-like proteins, and Vitamin B5 pantothenate, all previously reported in different Clade 12 PPN ( de Almeida Engler et al 1999 ; Haegeman, Jones, et al 2011 ) were identified. Interestingly, classes of enzymes, such as GH28 polygalacturonases, observed in root-knot nematodes ( Jaubert et al 2002 ) and their close relatives in the family Pratylenchidae ( Haegeman, Joseph, et al 2011 ; Bauters et al 2014 ), but not in cyst nematodes, were identified in N. aberrans . Conversely, other classes of enzymes, such as GH53 candidate arabinogalactanase, reported in cyst nematodes ( Vanholme et al 2009 ) and suggested to be present in Pratylenchidae ( Haegeman, Joseph, et al 2011 ) but not in root-knot nematodes, were also found in N. aberrans ( table 1 ).…”
Section: Resultsmentioning
confidence: 99%